Real-time cheating immune secret sharing for remote sensing images - Shivani, Shivendra; Patel, Subhash Chandra; Arora, Vinay; Sharma, Bhisham; Jolfaei, Alireza; Srivastava, Gautam (Journal of real-time image processing, 2021)
To observe the earth surface and its atmospheric interaction, various advanced optical and radar sensors are utilized. This observation returns a huge amount of optical multidimensional remote sensing images which may be used in multidisciplinary fields. The processing of these images in real time is a challenging task because of their high spatial resolution and complex data structure. At the same time, these images are quite confidential in various applications such as in the military and intelligence sectors. For secretly transmitting the remote sensing images in real time, a real-time cheating immune secret sharing approach is introduced in this paper. The proposed approach minimizes the time as well as space complexity for the secret sharing effectively. It also generates meaningful shares without the restriction for any fixed number participants. Generated shares by the proposed approach are cheating immune. That means they can authenticate themselves if tampered with. Experimental results show the effectiveness of the proposed approach.